Compressive strength of rubberized-ultra high performance concrete with different elevated temperature - Haikal Ikmal, Rahimee (2018)
Advance in technology makes the concrete material led to the development of new type of cementitious composites which known as Ultra High Performance Concrete (UHPC). UHPC is a type of concrete known by its exceptionally high strength and durability. The waste materials were determined as material that can cause problem to the environment. The waste materials can be reduced by processing them in construction materials such as UHPC. The waste material used in this study was waste crumb tyre (WCT). The objective in this study to determine the compressive strength of rubberized UHPC at different elevated temperatures such as 100˚C, 150˚C and 200˚C and determine the weight loss of rubberized UHPC subjected to pre-heating condition. The waste crumb tyre were modified on surface treatment by using NaOH with duration of 20, 40 and 60 minutes. The waste crumb tyre were used as replacement for coarse aggregate in 5% of percentage from total weight of coarse aggregate and will be mixed together to make rubberized UHPC with fixed 5% percentage of WCT. Based on the result, it can be concluded that the rubberized UHPC with surface treatment 60 minutes or rubberized UHPC-60 is the best with strength and weight loss compared to other rubberized UHPC surface treatment.